Pengaruh Service Marketing Mix Terhadap Keputusan Pembelian Paket Perjalanan Wisata Ke Luar Negeri Pada Biro Perjalanan Wisata Di Surabaya - Agustin, Yeni (Tourism Retailing+, 2013)
Nowadays, the number of Surabaya people who did travel abroad is increasing. Most of them decided to buy an outbound package tour from a travel agent in Surabaya. In order to increase the sales volume, a travel agent is needed to analyze some factors that influencing the buying decision. Therefore, this research was conducted to analyze those factors based on 7Pâs marketing mix. The purpose of the research is to find out whether consumer buying decision is affected by 7Pâs significantly or not. Besides, the variable dominant will be known as well. Quantitative â descriptive was used in this study. In Which respondents who have been selected were those people who live in Suarabaya and have been joined an outbound tour in last 3 months. For the sampling method, non probability sampling through the judgemental sampling was chosen. Questionnaire was used to collect the data and processed it in SPSS 17.00 using statistic descriptive and multiple linear regression. The result of this research indicates that consumer buying deision is influenced by seven variables which work together. But separately, consumer buying decision isnât affected by Process and Physical Evidence. Only Price, Place, People, Product and Promotion that give the significant influence.